Identification of Self Incompatibility (S) Alleles in Turkish Apple Gene Sources using Allele-specific PCR - Mohammad Hasanzadeh; Merve Dilek Karataş; Nahid Hazrati; Canan Yüksel Özmen; Serdar Altıntaş; Mehmet Emin Akçay; Ali Ergül (Journal of Agricultural Sciences)
Self-incompatibility (SI) is a genetic mechanism in many flowering plants by which generative reproduction is prevented. The self-incompatibility caused by the genetic functions of the cell is controlled by genes called S genes or self-incompatibility genes. Self-incompatibility results in decreased pollination and ultimately yield loss. In apple (Malus domestica L.), self-incompatibility is controlled by multi-allelic S-locus. Approaches in the S-glycoprotein profiles and allele-specific PCR methods using the gene profiles and S-glycoprotein profiles for determination of the incompatibility levels are of great importance. In current study, the self-incompatibility status of 192 apple genotypes (such as, Amasya, Hüryemez, Şah elması, Tokat, Demir elması etc.) obtained from the National Collection of Atatürk Horticultural Central Research Institute, Yalova, Turkey, has been determined. For this purpose, genotype-specific allele status and compatibility levels were screened via PCR (Polymerase Chain Reaction) using 4 different S-alleles (Sd, Sf, S26 and S9). 181 genotypes containing at least 1 S-allele were identified as ‘Partially Incompatible’ and 12 genotypes involving 4 S-alleles were assigned ‘Totally Incompatible’. No S-alleles were observed in 2 genotypes (Pancarlık and Hüryemez) which exhibited ‘Compatibility’ status.